A search for neutral high-mass Higgs bosons decaying into pairs of hadronically decaying tau leptons in 13 TeV collisions recorded by the ATLAS detector - Pickering, M (2016)
This thesis outlines the search for neutral Higgs bosons in a mass range of mH/A = 200 GeV − 1.2 TeV, decaying to a pair of hadronically decaying tau leptons. The search is performed using √s = 13 TeV proton-proton collision data, corresponding to an integrated luminosity of 3.21 fb−1, recorded by the ATLAS detector. No excess over the predicted Standard Model background is observed and upper limits are placed on the production cross section times branching fraction as a function of the mass of the scalar resonance. When combined with the results of the analysis where one of the tau leptons decays to either a muon or electron, the 95% confidence level upper limit on the cross section times branching fraction ranges from 1.4 pb at mH/A = 200 GeV to 0.025 pb at mH/A = 1.2 TeV for a scalar boson produced via gluon-gluon fusion, and 1.6 pb at mH/A = 200 GeV to 0.028 pb at mH/A = 1.2 TeV for a scalar boson produced via b-associated production. The results are interpreted in the Minimal Supersymmetric extension to the Standard Model (MSSM) as a limit on the value of tanβ, as a function of the mass of the neutral CP-odd MSSM Higgs boson. In the mmod+ scenario, the 95% confidence level upper limit is tanβ < 7.6 for mA = 200 GeV, and tanβ < 47 for mA = 1 TeV. For the mass range mA > 500 GeV, the upper limit on tanβ is improved in comparison to previous ATLAS searches.